Epidemiology education: classification of courses - Houssein, Naeima (Interdisciplinary Journal of Epidemiology and Public Health, 2025)
Public health around the world faces significant health challenges every day. Epidemiology is one of the tools of public health and preventive medicine. There is a crucial need to develop epidemiology education and training programs according to the needs of each episode - which is dynamic - to cover the complex web of diseases and provide the most accurate answers in real-world public health. In reviewing several existing epidemiology degree programs worldwide, an overlap in some basic public health and epidemiology courses was observed. Effective epidemiology training programs are based on acquiring knowledge of the core competencies of epidemiology in three parts: 1. epidemiological methods and measures, 2. branches of epidemiology, and 3. supporting courses. A precise classification of courses, whether at the undergraduate or graduate level, can improve the design of the curriculum. In addition, different teaching approaches and continuous program evaluation are highly recommended. Therefore, effective epidemiology training programs require a carefully designed curriculum that integrates epidemiological methodology and measures and their applications in different branches of public health, supported by biostatistics and health informatics skills.